If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1=3x-1
We simplify the equation to the form, which is simple to understand
1=3x-1
We move all terms containing x to the left and all other terms to the right.
-3x=-1-1
We simplify left and right side of the equation.
-3x=-2
We divide both sides of the equation by -03 to get x.
x=0.666666666667
| 2(v-7)-4v=4 | | 24x^3-14x^2-x+1=0 | | 35/8= | | 6u^2+13u+5=0 | | 2=-3x+8 | | 49=9y-68 | | 6xy=3x^2 | | y=-3(3)+8 | | 6x+42=2x-2 | | 2y-3+5y=y+15 | | 3x+6y=45 | | 2,295=-74t | | 7y+8(y+6)= | | 3*x+6=5*x | | 8c-4=2-4c | | (x+2)(2x+1)=(x+6)(2x+3) | | 18w=234 | | -27=-7w+4(w-6) | | 4y^2-8y+9=0 | | 14-(5x-6)=-6(x+1)-5 | | (x+1)(x-3)=4 | | [x]=7 | | 4(2x+3)=6(x+3) | | 8=2v+6 | | .5(1-2.5y)+1.25y=.5 | | -17=n/4-13 | | .8(3v-2w)+.2(7v-2w)= | | 3y=7+5 | | -9y-3=-8y-7 | | 11x+8=4x-6 | | 5w^2+41w+42=0 | | n+15=30 |